Pengaruh Media Permainan Blessing Box Terhadap Pemahaman Makna Perlengkapan Puja Siswa SMB Dharma Giri Mulia di Desa Tanjung Pinang Kabupaten Paser - Wandi Wijaya; Wina Dhamayanti; Adji Sastrosupadi (Dhammavicaya : Jurnal Pengkajian Dhamma, 2025)
Buddhist education plays a crucial role in shaping students' character and spiritual understanding. However, learning in Buddhist Sunday Schools often faces challenges such as monotonous teaching methods, which reduce student interest and comprehension, particularly regarding puja (worship) equipment. Items like candles, incense, and flowers hold deep symbolic meaning in Buddhism, yet students' understanding remains low. This study examines the effectiveness of the Blessing Box game as an innovative solution to enhance student comprehension. A quantitative experimental method was employed, with 18 respondents. Data was collected through questionnaires and analyzed using a Likert scale and paired t-test. The results showed a significant improvement in students' understanding after using the Blessing Box, with an achievement rate of 83.85% (highly understood category). The t-test confirmed a highly significant increase (t-value 18.71 > t-table 2.89), with a mean score difference of 20.38 between pre-intervention (59.44) and post-intervention (79.83). The findings indicate that Blessing Box effectively enhances students' comprehension. Teachers are advised to maintain and develop this media with more inclusive variations. Future research could expand the sample size or test the media’s effectiveness on other religious materials. This study proves that interactive learning through games can significantly improve student understanding.